2015
DOI: 10.1589/jpts.27.2039
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity and health status with intelligence quotient of high school students in Jeddah

Abstract: [Purpose] The present study investigated the relationships of physical activity and healthiness with the intelligence quotients of high school students in Jeddah. [Subjects and Methods] A total of 135 male and female students were randomly drawn from public and private secondary schools in Jeddah. A self-designed questionnaire was distributed to the students that included demographic, physical activity, and health status sections. Body mass index measurement and an intelligence quotient test were carried out f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Fifty‐one studies met the inclusion criteria and were included in the literature review. All these studies were observational studies, 50 were cross‐sectional 17–66 and one was a case‐control design 67 . Seventeen were published in national journals and 34 in international journals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty‐one studies met the inclusion criteria and were included in the literature review. All these studies were observational studies, 50 were cross‐sectional 17–66 and one was a case‐control design 67 . Seventeen were published in national journals and 34 in international journals.…”
Section: Resultsmentioning
confidence: 99%
“…However, significant interstudy heterogeneity was noted (I 2 = 72%) owing to differences in evaluation parameters. On the other hand, the association between father education and the prevalence of overweight and obesity in Saudi adolescents was reported in six studies 25,26,37,47,58,60,61 that indicated a statistically significant ( P = .0005) positive association between fathers with the highest level of education and odds of overweight and obesity (Table 3, Figure 5F). Low interstudy heterogeneity was noted (I 2 = 10%).…”
Section: Discussionmentioning
confidence: 98%
“…As mentioned previously, the optimal level of physical activity has been reported to improve cognitive function [1][2][3]. In childhood, physical activity is associated with the intelligence and emotional quotients [16][17][18]. Latorre Román et al in 2017 [33], reported the association between physical fitness and creativity in elementary school children (n = 308, age from 8 to 12 years).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cognitive function, brain function and academic achievement have been reported to be associated with physical activity [13][14][15]. The association between physical activity, healthiness, and the intelligence quotients of 135 high school students in Jeddah in the Kingdom of Saudi Arabia was reported, and the findings indicated that the intelligence quotient was positively associated with physical activity and health status [16]. In addition, there is evidence that demonstrates a positive link between the emotional quotient and physical activity in 599 Taiwanese college students [17].…”
Section: Introductionmentioning
confidence: 97%
“…These reports 20 , 21 ) showed the relationship between IQ and executive function test scores, and supported the results of this research. Meanwhile, IQ in late adolescence has been found to be strongly correlated with PA and health 22 ) . Importantly, while we observed a correlation between VIQ and total energy expenditure (r=0.35), we observed no relationship between IQ and number of steps.…”
Section: Discussionmentioning
confidence: 99%